QADHA DAN QADAR MANUSIA DALAM AL-QUR’AN - Dikla, M Fathi; Abdul Rasyid Ridho (el-Umdah, 2024)
The intellectual conflict of the mutakallimin was related to qadha and qadar, one of which was caused by differences in interpretation of verses and habits related to qadha and qadar. Understanding qadha and qadar in Islam greatly influences the process of human life, both worldly life and the hereafter. Differences in understanding of qadha and qadar or destiny gave birth to three different groups of understanding. The first group believes that everything humans do is forced by God, humans do not have any role in their actions. This group is led by Jabbariyah. The second group holds the view that all human actions are the free will of humans themselves, without God's intervention. This group is represented by the Qadariyyah and Mu'tazilah. These two groups are 180 degrees opposite. Then a mediating group emerged who held the view that destiny is God's provision which humans must accept and still prioritize God's will. If humans will, then God's will is the main thing. These three theological schools have a strong basis in the Koran in their defense of their opinions. This research wants to analyze the meaning of qadha and qadar in the Koran in a comprehensive manner. This research uses literature review techniques and maudhu'i (thematic) methods in analyzing verses related to qadha and qadar. The researcher expressed the views of several commentators in interpreting the words qadha and qadar, including the opinions of Buya Hamka, M. Quraish Shihab, Fakhruddin Ar-Razi, Sayyid Qutub, and Muhammad Husain Thabathaba'i. They have slight differences in the meaning of qadha and qadar, but they are the same in interpreting qadha and qadar as everything that happens in the universe is the provisions, regulations, levels and measurements that Allah SWT has set for His creatures.